Atlas of crabs of the Persian Gulf - Naderloo, Reza (Springer, 2017)
This illustrated atlas describes 256 extant brachyuran crab species in the Persian Gulf and the Gulf of Oman. Identification keys are provided for 37 brachyuran families, 142 genera and 256 species on the basis of their main synapomorphies. Brief but precise descriptions highlighting the main characteristics are also provided for every family. The atlas displays features high-quality color photos, offering a hands-on guide and equipping readers to readily diagnose crab species in the region. Importantly, a line drawing of the first male gonopod, as well as its main diagnostic characteristics, are provided for all species. Further, every species is supplemented with synonymies that encompass the original descriptions, overall revision of the given taxa, monographs and all records from the northwestern Indian Ocean including the Persian Gulf and the Gulf of Oman. For each species, the book provides detailed local and global distribution maps, together with important ecological data including habitat preference. Further, it includes a general introduction to the brachyuran crabs with schematic drawings of their external morphology, as well as a comprehensive introduction to the Persian Gulf and the Gulf of Oman as marine ecoregions (geography, hydrology, biology, and environmental condition). The book offers an indispensable guide for all professionals, researchers, and students interested in brachyuran crabs around the globe and particularly in the Persian Gulf and the Gulf of Oman.
Keywords: Crabs -- Persian Gulf -- Atlases.; Persian Gulf.; elektronické knihy; electronic books